Electrochemical performance of new hybrid activated carbon materials from binary and ternary Date-Olive pits for supercapacitor electrodes. (March 2022) - Ait Kaci Azzou, Katia; Terbouche, Achour; Ait Ramdane-Terbouche, Chafia; Belkhalfa, Hakim; Bachari, Khaldoun; Hauchard, Didier; Mezaoui, Djillali
Highlights: Binary Date-Olive and ternary Date-Olive-Sugar pits are used to prepare activated carbons (ACOD and ACODS ) for supercapacitor. The materials were characterized by ATR-FTIR, SEM, Raman, XRD, Laser diffraction and electrochemical methods. The electrode based on ACODS exhibited high specific energy (36.82 Wh.kg −1 ) and specific power (107.78 W.kg −1 ). The stability of ACODS electrode showed high cycle stability with 96.5% capacitance retention. Abstract: In the present work, hybrid composites have been proposed as electrode materials for supercapacitor. Therefore, this work is focused on the simple preparation without catalyst of low-cost binary and ternary activated carbons derived from agricultural waste such as Algerian date and olive pits, which give excellent results with high specific power and high specific energy. The binary Olive-Date and ternary Olive-Date-Sugar materials have been prepared using a planetary crusher and their corresponding activated carbons (ACOD and ACODS ) were characterized by ATR-FTIR, BET, SEM, Raman, XRD, Laser diffractionand electrochemical methods. The electrochemical results showed that ACOD has a specific capacitance of 104.10 F.g −1 at 0.3 A.g −1 with specific energy of 17.56 Wh.kg −1 . However, the ternary material (ACODS ) demonstrated outstanding performances with excellent specific capacitance (528 F.g −1 at 0.3 A.g −1 ) and high specific energy (36.82 Wh.kg −1 ) as well as a high stability for 10, 000 charge-discharge cycles at 10 A.g −1, with a capacitance retention of 89.6%. EIS measurements showed that the ACODS material shows lower charge transfer resistance (19.4 Ω). Based on the above parameters, this study revealed a huge capacity of the new activated carbon material (ACODS ) to obtain stable high-performance supercapacitor electrode for energy storage. Graphical abstract: Image, graphical abstract